Brand-Consumer Storytelling Theory and Research: Introduction to a Psychology & Marketing Special Issue - Woodside, Arch (John Wiley & Sons, 2010)
This introduction reviews core principles of storytelling theory. The article explains basic propositions of good storytelling. A brief summary of each of the six articles that follow appears. The article extends a note of appreciation to the members of the special editorial board for this issue and to Rajan Nataraajan.